Carbon dots incorporated metal–organic framework for enhancing fluorescence detection performance - Liu, Xiqing; Zhou, Zhiping; Wang, Tao; Deng, Pengyin; Yan, Yongsheng (Journal of materials science, 2020)
The fluorescence detection of environmental pollution residues is hugely significant; thus, the improvements in sensitivity and selectivity are still a great task. In this work, a novel molecularly imprinted fluorescence sensor (CDs&ZIF-8@MIPs) with a core–shell structure was prepared for the highly sensitive and selective quantification of malachite green (MG). The high sensitivity was contributed from carbon dots (CDs) as the fluorescence materials and ZIF-8 nanoparticles served as the support materials to ameliorate the dispersibility of CDs. The high selectivity is mainly derived from fabricating thin molecular imprinting polymers in ZIF-8 surfaces. Under the optimum conditions, CDs&ZIF-8@MIPs displayed rapid reaction time (2.0 min), lower detection limit (2.93 nM) with the concentration linear range of 20–180 nM and high selectivity to MG among MG analogs. Importantly, the developed monitoring method was successfully applied to MG determination with the satisfactory recoveries in environmental water samples. This present work effectively improved the sensitivity and selectivity of fluorescence sensors for MG detection.